2004
DOI: 10.1080/09513590400021227
|View full text |Cite
|
Sign up to set email alerts
|

Current and lifetime psychiatric illness in women with Turner syndrome

Abstract: Abnormalities in quality of life and cognitive measures have been observed in women with Turner syndrome (TS), and a relationship between these phenomena and chromosomal constitution has been suggested. In contrast, few studies have systematically evaluated the presence of mood and behavioral syndromes in these women. In this study, 100 TS women were administered the Structured Clinical Interview for DSM IV after a two-week period during which their hormone replacement had been discontinued. The majority of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
2
10

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 53 publications
2
66
2
10
Order By: Relevance
“…Results revealed that women with TS had a higher rate of lifetime depression than the general population [Cardoso et al 2004]. With respect to self-esteem, results showed that women rated lower on Rosenberg's scale than the normal control group yet exhibited similar levels of self-esteem as 46,XX women with infertility due to premature ovarian failure [Cardoso et al 2004].…”
Section: Sample Characteristicsmentioning
confidence: 89%
See 1 more Smart Citation
“…Results revealed that women with TS had a higher rate of lifetime depression than the general population [Cardoso et al 2004]. With respect to self-esteem, results showed that women rated lower on Rosenberg's scale than the normal control group yet exhibited similar levels of self-esteem as 46,XX women with infertility due to premature ovarian failure [Cardoso et al 2004].…”
Section: Sample Characteristicsmentioning
confidence: 89%
“…Depression was assessed by the administration of the DSM IV Structured Clinical Interview and self-esteem was measured using the Rosenberg self-esteem scale [Rosenberg 1965;First et al 1995]. Results revealed that women with TS had a higher rate of lifetime depression than the general population [Cardoso et al 2004]. With respect to self-esteem, results showed that women rated lower on Rosenberg's scale than the normal control group yet exhibited similar levels of self-esteem as 46,XX women with infertility due to premature ovarian failure [Cardoso et al 2004].…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Al no existir ovarios funcionantes se ve imposibilitada su capacidad de lograr la maternidad por medios naturales, siendo necesario recurrir a métodos artificiales de fecundación. Esta situación produce un gran impacto tanto a nivel psicológico como social a causa de la relevancia que tiene en relación al rol y al ideal femenino la posibilidad de la maternidad (Cardoso et al, 2004;Sartori, López & Aguilar, 2013).…”
Section: Introductionunclassified
“…Some studies have used parental evaluations and self-reporting for assessment of psychiatric issues in TS patients. They suggested psychiatric comorbidities especially anxiety and depression in TS patients (Catinari et al, 2006;McCauley et al, 2001;Kilic et al, 2005;Lasaite et al, 2010;Cardoso et al, 2004). In one report; the TS parents reported that TS girls were less socially competent than the controls (McCauley et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies (Kilic et al, 2005;Lasaite et al, 2010) reported that TS girls had significantly higher anxiety levels and impaired cognitive functions than age-matched controls. Another large study (Cardoso et al, 2004) reported that 52% of the TS women met criteria for a current or a past depressive or anxiety disorder and 18% of TS cases met criteria for psychiatric disorder, including major and minor depression and Anxiety. The majority of the previous studies on TS personality had indistinct mixed statistical data; with sometimes conflict results (Catinari et al, 2006).…”
Section: Introductionmentioning
confidence: 99%